Development and Characterization of Chemical Cochleostomy in the Guinea Pig. (June 2015) - Alyono, Jennifer C.; Corrales, C. Eduardo; Huth, Markus E.; Blevins, Nikolas H.; Ricci, Anthony J.
Objectives: Creation of an atraumatic, hearing-preservation cochleostomy is integral to the future of minimally invasive inner ear surgery. The goal of this study was to develop and characterize a novel chemical approach to cochleostomy. Study Design: Prospective animal study. Setting: Laboratory. Methods: Experimental animal study in which phosphoric acid gel (PAG) was used to decalcify the otic capsule in 25 Hartley guinea pigs. Five animals in each of 5 surgical groups were studied: (1) mechanically opening the auditory bulla alone, (2) PAG thinning of the basal turn otic capsule, leaving endosteum covered by a layer of bone, (3) micro-pick manual cochleostomy, (4) PAG chemical cochleostomy, exposing the endosteum, and (5) combined PAG/micro-pick cochleostomy, with initial chemical thinning and subsequent manual removal of the last osseous layer. Preoperative and postoperative auditory brainstem responses and otoacoustic emissions were obtained at 2, 6, 10, and 16 kHz. Hematoxylin and eosin–stained paraffin sections were compared. Results: Surgical and histologic findings confirmed that application of PAG provided reproducible local bone removal, and cochlear access was enabled. Statistically significant auditory threshold shifts were observed at 10 kHz ( P = .048) and 16 kHz ( P = .0013) following cochleostomy using PAG alone (group 4) and at 16 kHz using manual cochleostomy (group 3) ( P = .028). No statistically significant, postoperative auditory threshold shifts were observed in the other groups, including PAG thinning with manual completion cochleostomy (group 5). Conclusion: Hearing preservation cochleostomy can be performed in an animal model using a novel technique of thinning cochlear bone with PAG and manually completing cochleostomy.